2022
DOI: 10.3390/molecules27020502
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin as a Modulator of Nrf2, NF-κB, and Their Crosstalk: Molecular Mechanisms and Possible Clinical Applications

Abstract: Astaxanthin (AST) is a dietary xanthophyll predominantly found in marine organisms and seafood. Due to its unique molecular features, AST has an excellent antioxidant activity with a wide range of applications in the nutraceutical and pharmaceutical industries. In the past decade, mounting evidence has suggested a protective role for AST against a wide range of diseases where oxidative stress and inflammation participate in a self-perpetuating cycle. Here, we review the underlying molecular mechanisms by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 123 publications
(139 reference statements)
1
29
0
3
Order By: Relevance
“…Our results showed that tissue SOD levels were lower in rats given DOX than in rats in the control group. This was in line with other studies [30,31]. However, THY pre-treatment reversed the observed change in SOD levels.…”
Section: Thymoquinone's Effects On Dox-induced Oxidative Stress Marke...supporting
confidence: 93%
“…Our results showed that tissue SOD levels were lower in rats given DOX than in rats in the control group. This was in line with other studies [30,31]. However, THY pre-treatment reversed the observed change in SOD levels.…”
Section: Thymoquinone's Effects On Dox-induced Oxidative Stress Marke...supporting
confidence: 93%
“…The latter findings impose the anti‐inflammatory potential of ambroxol (200 mg/kg) in the injured rat colons. It has been well delineated that NF‐κB/Nrf2 crosstalk is a significant player in the interplay between oxidative stress and inflammation 58 . In this context, ambroxol proved to modulate NF‐κB/Nrf2 crosstalk.…”
Section: Discussionmentioning
confidence: 98%
“…It has been well delineated that NF-κB/Nrf2 crosstalk is a significant player in the interplay between oxidative stress and inflammation. 58 In this context, ambroxol proved to modulate NF-κB/Nrf2 crosstalk. As indicated by the alterations in the levels of Nrf2, Nrf2 activity, HO-1, the ratio of phospho p65/p65, NF-κB p65 binding activity, and increased levels of IκBα as well as the consequent elevations in the activity of catalase and the total antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another survey showed that AST can significantly increase the activity of GPx and SOD, protecting mouse hepatocytes from oxidative damage by using hydrogen peroxide [24]. Fakhri et al also found that AST can increase the expression of glutathione S-transferase α1 (GST-α1), which enhances the biological defense against oxidative stress damage via the activation of the extracellular signal-regulated protein kinase (ERK) signaling pathway in vitro and in vivo [10].…”
Section: Main Biological Activities Of Astmentioning
confidence: 99%
“…Due to the speci c biological structure, AST can play an important role in a variety of biological processes, such as antioxidant, anti-in ammatory, antiapoptotic, and anticancer processes; it has a series of biological functions, such as protecting the cardiovascular system, delaying diabetic nephropathy and liver injury, having antiobesity properties, and improving immunity [10]. Currently, AST has become a hot research topic, and several recent studies have highlighted the potential protective role of AST in eye diseases.…”
Section: Introductionmentioning
confidence: 99%